Territorializing International Travel Emissions: Geography and Magnitude of the Hidden Climate Footprint of Brussels - Boussauw, Kobe (2021)
In the present article we investigate the geography and magnitude of the climate footprint of long-distance travel with Brussels, Belgium, as a destination. The internationally networked position of this city goes hand in hand with a strong dependence on international mobility, which largely materializes in impressive volumes of long-distance travel and associated consumption of important amounts of fossil fuel. Despite a surge in concerns about global warming, the climate footprint of most international travel, notably air travel, is not included in the official national and regional climate inventories, or in other words, it is not territorialized. The official climate footprint of the Brussels-Capital Region attained 3.7 Mton CO2eq per year (in 2017). Based on our exploratory calculations, however, the total estimated climate footprint of all Brussels-bound international travel equalled an additional 2.7 Mton CO2eq. In terms of geographical distribution, over 70% of international travellers to Brussels come from Europe, while these represent only 15% of the climate footprint of all international travel to Brussels. We conclude that the practice of not allocating emissions caused by international travel to territorial units has kept the magnitude and complexity of this problem largely under the radar and contributes to the lack of societal support for curbing growth of international aviation.